PENINGKATAN KINERJA DAN EFISIENSI OPERASIONAL di INDUSTRI PEMINTALAN - Parmawati, Sih; Dyah Novia Nugraheni; Bambang Yulianto (Bajang Institute, 2025)
This study explores the impact of Team Leader’s interpersonal communication on the effectiveness and efficiency of team performance in the spinning industry. Initial observations revealed that production efficiency remains suboptimal and frequent miscommunication occurs between the Team Leader and team members. Employing a descriptive-analytical method with a 5W1H framework, data were collected through structured questionnaires distributed to 30 randomly selected respondents, as well as interviews and field observations. Findings indicate that while the Team Leader shows a high level of openness to team input, the quality of feedback and clarity in instruction delivery remain insufficient. Team effectiveness was rated as moderate, and operational efficiency was identified as an area requiring significant improvement. Key communication barriers include mismatched task assignments outside the established job description, inadequate documentation, and the lack of a structured feedback mechanism. The study recommends implementing interpersonal communication training, developing formal feedback systems, and maintaining consistent documentation during daily briefings. These steps are expected to support the development of a more effective communication structure and enhance performance outcomes, particularly in textile manufacturing environments